PENGARUH PENGETAHUAN PASAR MODAL, PERSEPSI RISIKO INVESTASI, PENGGUNAAN TEKNOLOGI TERHADAP PERILAKU MAHASISWA BERINVESTASI DI PASAR MODAL (Studi Empiris pada Galeri Investasi di Purwokerto) - Gede Ari Slamet Suaputra; Irianing Suparlinah; Sujono Sujono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This study aims to determine and analize effect of capital market knowledge, risk investment perception and use of technology towards the student’s investing behavior in the capital market. The population is the student’s who are members of the Investment Gallery Universitas Jenderal Soedirman and Islamic Investment Gallery Universitas Muhammadiyah Purwokerto. The sampling method used is purposive sampling. The data sample was obtained as many as 143 respondents. The result of this research indicates that capital market knowledge has a positive impact to the student’s investing behavior in the capital market, risk investment perception and use of technology have no impact to the student’s investing behavior in the capital market. Implication of the research is the most basic student’s must have as the investor. Investors need a basic understanding of the capital market, stocks as an investment in the capital market and rate of returns. Knowledge will support skills in analyzing, choosing and making a decision.